Genome-wide analysis of the SBT gene family involved in drought tolerance in cotton - Dai, Maohua; Zhou, Na; Zhang, Yue; Zhang, Yuexin; Ni, Kesong; Wu, Zhenliang; Liu, Liying; Wang, Xiaoge; Chen, Quanjia (Frontiers in Plant Science, 2023)
The subtilisin-like proteases (SBTs) are a large family of serine peptidases that are unique to plants. Previous studies have shown that SBTs are associated with developmental processes and environmental responses. However, comprehensive identification and systematic analysis of the SBT family have not been conducted in cotton. In this study, we identified 120 and 112 SBTs in the tetraploid cotton species G. hirsutum and G. barbadense, while 67 and 69 SBTs were identified in the diploid species G. arboreum and G. raimondii, respectively; these SBTs were divided into five distinct subfamilies. We used bioinformatics methods to analyze the structural characteristics, phylogenetic relationships, gene structures, expression modes, evolutionary relationships, selection pressures and stress responses of SBT gene family members in upland cotton. We identified the SBT gene GhSBT27A, and explore its function through virus-induced gene silencing and transmission electron microscopy . These results suggested that the GhSBT27A gene was involved in the response to drought stress. These results lay a foundation for further study on the drought stress mechanism of cotton.